Microbial fuel cell performance improvement based on FliC-deficient E. coli strain. (December 2020) - Nguyen, Dang-Trang; Tamura, Teppei; Tobe, Ryuta; Mihara, Hisaaki; Taguchi, Kozo
Abstract: FliC-deficient Escherichia coli ( E. coli ) strain ( △ fliC) and its parent strain, wildtype K-12 (WT), were utilized to produce electricity in microbial fuel cells (MFCs). Although the two strains had similar growth curves, the biofilm of △ fliC generated a 193 % higher power density than that of WT. The biofilm formation test revealed that △ fliC was better than WT in biofilm formation on the anode in terms of bacterial cell concentration. This result provides valuable insight into the improvement of electricity production by E. coli -inoculated MFCs.